The Evaluation Of Unconfined Groundwater Quality At Air Dingin Landfill in Padang City - Taqdir Alamsyah; Muh Anhar; Desmon Hamid; Yusuf Yusuf; Yuli Yetri (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
An evaluation of unconfined groundwater at the Air Dingin Landfill (TPA) in Padang City, West Sumatra, has been conducted to assess the impact of leachate on the water quality utilized by the surrounding community. Groundwater samples were collected from ten strategically selected points around the landfill, with support from JPS. The leachate characteristics analyzed included pH, temperature, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), total dissolved solids (TDS), total suspended solids (TSS), and the concentrations of heavy metals such as Pb, Cu, Mn, As, Cd, Cr, and Fe. A thermometer and a pH meter were employed to measure temperature and pH levels, respectively. The concentrations of heavy metals were determined using Atomic Absorption Spectroscopy (AAS), while BOD, COD, TDS, and TSS values were assessed through the gravimetry method.The test results for various parameters, including odor, taste, temperature, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and levels of heavy metals (Pb, Cu, Mn, As, Cd, Cr, and Fe), generally remain below the quality standards outlined in Indonesian Minister of Health Regulation No. 416 of 1990 and Government Regulation No. 82 of 2001. However, the pH levels of the unconfined groundwater measured between 3.04 and 6.05, which do not meet the Government's requirements for all test wells. Additionally, the leachate does not appear to impact the quality of the unconfined groundwater surrounding the Air Dingin Landfill. Overall, the groundwater quality in this area generally complies with the standards set forth in Minister of Health Regulation No. 416 of 1990 and Government Regulation No. 82 of 2001..